Intercultural sensitivity among medical students of UniKL RCMP - Ramlan, Farah Ayuni; Kassim, Nilam Maisarah; Pakirisamy, S.; Selvakumar, Vishalini (2014)
Generally the development and spread of technology has helped to minimize the physical borders among people.Knowledge, technology, education and even cultures have been easily transferred across borders through globalization.It is believed that educational institutions provide stable platforms to promote and practice intercultural communication among the younger generation of students.This study aims to examine whether medical students of UniKL RCMP have developed the required level of intercultural sensitivity to develop better intercultural understanding and communication across cultures.The Intercultural Sensitivity Inventory (Penbek, Yurakul & Cerit, 2009) was used to quantify participant’s levels of intercultural sensitivity based on Chen and Starosta (2000).Results of this study show that medical students have moderate level of intercultural sensitivity.Formal education/instruction does play an essential role in raising cultural awareness among students.